Internet of Things in Higher Education - Mansirat Kaur, Harleen Kaur, Saranjeet Kaur , Amandeep Singh (International Journal of Advanced Science and Technology, 2020)
In the coming years, technology will leave a great impact on education. Internet Of Things Plays avital role in education. Most of the institutes take help of IoT to provide smart classes to students andto enhance their learning experience outcomes. With the growing vogue of IoT, the wearable devicesare made for students with small sensors to connecting them with learning system. IoT enhances thelearning system by providing the small gadgets to the students like:-IPad, electronic white boards,Laptops, Tablets and eBooks by using these gadgets teachers can interact with students. By usingthese digital transformation devices will reveal new awareness that will change the learning andimplement things used in education system.